An evaluation of the impact of community participation and multi-organisational partnerships on the implementation of sector policing in the rural areas of the Limpopo Province - Baloyi, Nyiketani Jackson (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPA)--Stellenbosch University, 2013.